A bill to authorize the project for environmental restoration at Smith Island, Maryland : report together with minority views (to accompany S. 2984) (including cost estimate of the Congressional Budget Office). - United States. Congress. Senate. Committee on Environment and Public Works. ([Washington, D.C. : U.S. G.P.O., 2002)
"November 4, 2002." Shipping list no.: 2003-0060-P. Caption title. Mode of access: Internet.